2015
DOI: 10.1002/14651858.cd004203.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Urethral (indwelling or intermittent) or suprapubic routes for short-term catheterisation in hospitalised adults

Abstract: Suprapubic catheters reduced the number of participants with asymptomatic bacteriuria, recatheterisation and pain compared with indwelling urethral. The evidence for symptomatic urinary tract infection was inconclusive.For indwelling versus intermittent urethral catheterisation, the evidence was inconclusive for symptomatic urinary tract infection and asymptomatic bacteriuria. No trials reported pain.The evidence was inconclusive for suprapubic versus intermittent urethral catheterisation. Trials should use a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 59 publications
2
43
0
1
Order By: Relevance
“…Thus, catheter implantation, although it may lead to histological changes in the bladder wall, seems not to systematically alter bladder function in rats so that urodynamic measurements closely represent daily bladder function. Clinical data of indwelling suprapubic catheters, a comparable situation for the bladder, support findings of our animal study underlying the truly translational approach of the urodynamic model in fully awake animals after chronic catheter implantation.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, catheter implantation, although it may lead to histological changes in the bladder wall, seems not to systematically alter bladder function in rats so that urodynamic measurements closely represent daily bladder function. Clinical data of indwelling suprapubic catheters, a comparable situation for the bladder, support findings of our animal study underlying the truly translational approach of the urodynamic model in fully awake animals after chronic catheter implantation.…”
Section: Discussionsupporting
confidence: 76%
“…SPC appears to safeguard against some of the potential complications of urethral catheterization such as UTI and urethral stenosis, allowing assessment of spontaneous voiding and avoiding recatheterization after a failed attempt [44]. Although it has been suggested that SPC might be associated with lower rates of UTI and urethral stricture formation, less patient discomfort, and easier management, a Cochrane SR failed to demonstrate a lower risk of symptomatic UTIs with use of SPC [49]. A 3-d rather than a 7-d period of catheterization after a first episode of AUR in addition to a1-blocker treatment should be preferred, since longer catheterization time increases complication rates without significantly increasing TWOC success [32].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review including 42 trials indicated an advantage on suprapubic catheterization in terms of asymptomatic bacteriuria and pain compared to the urethral catheterization [ 13 ]. To our knowledge, UC was traditionally used in RP not only for the drainage of bladder but also for protecting the anastomosis and promoting healing.…”
Section: Discussionmentioning
confidence: 99%